Adaptation of clinical pharmacy services to meet patient care needs during the COVID‐19 pandemic. Issue 3 (28th January 2021) - Danelich, Ilya M.; Thomson, Lynda; Alberto, Judith; Bonanni, Shirley; Buckler, Rebecca; Foley, John; Phillips, Samantha; Rall, Braden; Thoma, Brandi; Merli, Geno; Wordell, Cindy
Abstract: The coronavirus disease 2019 (COVID‐19) pandemic caused by the severe acute respiratory syndrome coronavirus 2 has challenged health systems to find innovative ways of delivering patient care while protecting staff from infection with the virus. As the COVID‐19 pandemic has continued to evolve establishing "hot spots" in various areas of the country, clinicians have learned more about caring for these patients. This has required the Department of Pharmacy at Thomas Jefferson University Hospital to constantly update the approach it has taken during this time, and the guidance which is provided for the pharmaceutical care of these patients. Because Philadelphia was in the initial stages of the pandemic within the United States, operations within the Department of Pharmacy at Thomas Jefferson University Hospital needed to be redesigned. This brief report provides an example of the swift changes that were made in the pharmacy practice model at a large academic medical center. Herein we describe the impact of the pandemic on the Department of Pharmacy at Thomas Jefferson University Hospital with a focus on clinical and operations aspects. The areas that will be highlighted in this report represent areas that required rapid and transformational change to the operations and/or clinical care in order to protect the health of pharmacists and allow them to continue to provide the necessary level of patient care.